AN ANALYSIS OF PRONUNCIATION ERRORS OF ENGLISH CONSONANTS : /?/ and /ð/ BY THE STUDENTS OF THE ENGLISH EDUCATION STUDY PROGRAM OF UNIVERSITY OF BENGKULU. - Irianto, Nofpian Andesta; ., Imranuddin; Sabaruddin, Syafrizal (UNIB Press, 2018)
This research was aimed to know and to analyze how English students in University of Bengkulu, English Education Study program class A and B, academic year 2015/2016 pronounced English consonants /?/ and /ð/. The instrument used for collecting the data was recording. This research used qualitative and quantitative method. The result of this research showed most of English students pronounced English consonants /?/ and /ð/ incorrectly. It showed that the students were not good at pronouncing English consonants /?/ and /ð/ when they were located at the middle or at the final of the words. Based on the findings, the study concluded that the errors were caused by several reasons such as the sound of /?/ and /ð/ which did not exist in Bahasa Indonesia, the influence of similar sound with Bahasa Inonesia consonants /t/ and /d/, and also the carelessness